Modelling of tungsten contamination and screening in WEST plasma discharges. (13th September 2021) - Di Genova, S.; Gallo, A.; Fedorczak, N.; Yang, H.; Ciraolo, G.; Romazanov, J.; Marandet, Y.; Bufferand, H.; Guillemaut, C.; Gunn, J.P.; Gil, C.; Serre, E.; et al.
Abstract: The WEST experiment is currently operating with tungsten plasma-facing components and testing ITER-like divertor monoblocks. In order to support WEST experiments interpretation, numerical analyses were carried out. Starting from WEST experimental data, realistic background plasma conditions were reproduced through SolEdge-EIRENE and used as input for ERO2.0 simulations to investigate tungsten migration. Tungsten contamination due to the different plasma-facing components was modelled under different plasma conditions, highlighting a non-negligible contribution of tungsten coming from the tokamak main chamber. Tungsten penetration factor was computed and used as an indication for tungsten screening by the background plasma at the different tokamak plasma-facing components. Simulations showed the main chamber components to be very weakly screened. Light impurities charge was showed to influence not only tungsten sputtering, but also its probability to enter the confined plasma. Simulations results indicated that even when the tungsten source is not heavily influenced by self-sputtering, contamination of the confined plasma can be strongly impacted by it in low density background plasma conditions. Finally, a one-to-one comparison between tungsten visible spectroscopy at the lower divertor from experimental data and from synthetic diagnostics was performed, showing that it is possible to reproduce a realistic lower divertor signal following experimental evidence on light impurities asymmetry between the targets.